THE BRONZE MIRRORS OF NORTH-EASTERN SEMIRECHYE IN THE ERA OF THE URBAN CULTURE DEVELOPMENT (LATE 8TH – EARLY 14TH CENTURIES) - K. Yu. Markova (Вестник Кемеровского государственного университета, 2013)
The paper focuses on the cultural contacts of Semirechye peoples with the neighboring regions in the Middle Ages, basingon the analysis of the bronze mirrors ornaments found in the Talgar fortress (the medieval city of Talhir). The items of import can be identified and associated with the places of production by disriminating a number of artistic culture peculiarities of a particular country. The presence of imported items and borrowing décor elements from other countries show the development of aesthetic norms of the era and the level of culture of medieval towns.